Very intense non-static magnetic fields and particle production - Di Piazza, A.; Calucci, G. (Вопросы атомной науки и техники, 2001)
We present the calculation of the probability production of e⁺ - e⁻ pairs in a strong rotating magnetic field. By comparing this case with that in which the magnetic field changes only in strength, we conclude that for pair production the change of direction of the magnetic field is much more efficient than the change of its strength.